Spatial variation in food web structure in a recovering marine ecosystem. - Kyle J Krumsick; Jonathan A D Fisher (PLoS ONE)
Spatial heterogeneity in food web structure and interactions may reconcile spatial variation in population and community dynamics in large marine ecosystems. In order to assess food web contributions to the different community recovery dynamics along the Newfoundland and Labrador shelf ecosystem, we quantified species interactions using stable isotope mixing models and food web metrics within three sub-regions. Representative samples of each species caught in trawls and plankton tows were analyzed for stomach contents and stable isotope ratios (δ15N and δ13C) to parameterize isotope mixing models. Regional variation, highlighted by the diets of three economically important species, was observed such that the southern region demonstrated a variety of trophic pathways of nutrient flow into the higher food web while the diets of fish in the northern regions were typically dominated by one or two pathways via dominant prey species, specifically shrimp (Pandalus sp.) and hyperiids. Food web metrics indicated that the low-diversity northern regions had higher connectance and shorter food chain lengths. This observed regional variation contributes to our understanding of the role of specific forage species to the ecosystem which is an essential contribution towards ecosystem-based management decisions.